PENGARUH PENGGUNAAN KOMPOS ESEM (Effective System Emultion Microorganism) PADA PERTUMBUHAN Acacia mangium Willd DI HTI PT. FINNANTARA KABUPATEN SINTANG - Setiorini, Endang; Latifah, Siti; Manurung, Togar Fernando (Universitas Tanjungpura, 2014)
Acacia mangium Willd has been developed industrial forest (HTI) in Indonesia. It uses as raw material for paper, pulp, building construction, furniture, firewood, container and others.Based on the result by PT . Finnantara, Acacia mangium Willd was age 6 months still much below the standards of company that is 2.7 m due to low soil fertility , so it is necessary to attempt for the restore fertility of the soil using type of compost is ESEM (Effective Microorganism System Emultion ). The result showed that the plant Acacia mangium Willd treated compost providing value added high average better than control treatmen. The highest value for plant height increment is the T4 treatment (dose 700gr), which has an average height of 121,4cm as well as having the highest value component P in 216,72 and component N in 0,40. In every treatment has increased in diameter trunk was different and T0 (control) has greatest in 2,20cm. Eventhouhg T0 has a low value of P componen in 22.44 and N componen in 0,17, but It has been able to increase the diameter of the plants. Keyword : Acacia mangium Willd, HTI, compost ESEM (Effective System Emultion Microorganism).